Methods and applications of statistics in the atmospheric and Earth sciences - Balakrishnan, N. (New Jersey : John Wiley, 2013)
"Presenting a concise, well-rounded focus on the statistical concepts and applications that are essential for understanding gathered data in the earth and atmospheric sciences. Containing contributions from over 100 leading academics, researchers, and practitioners in these fields, this comprehensive book unveils modern, approaches to the acquisition and analysis of data across diverse subject areas like geology, agriculture, animal science, and geophysics. It discusses techniques related to survey methodology, computational statistics, and operations research and covers new areas of interest like non-linear weather forecasting, construction geological surveys, and water pollution assessment"--
"Provides a realistic alternative to the individual user who would like a quick reference containing encyclopedic information that pertains to their particular research interests and needs"--
Includes bibliographical references and index.
Keywords: Atmospheric physics -- Statistical methods; Earth sciences -- Statistical methods; MATHEMATICS / Probability & Statistics / General